PENGARUH MOTIVASI TERHADAP KINERJA PEGAWAI KABI PEMERINTAHAN PADA KANTOR DESA KARANG BINANGUN HELITANG MADANG RAYA OGAN KOMERING ULU TIMUR - Angela, Dona (Jurnal Trisna Riset, 2023)
Supporting the progress and development of an organization really needs to be done seriously and continuously in all fields and all aspects of life. The availability of quality human resources and a high work ethic is the main capital for an organization to be on par with other organizations. At the Karang Binangun Belitang Modang Raya Ogan Komering Ulu Timur Village Office, it turns out that motivation has not been implemented properly so that employee performance is not optimal. The problem faced is how motivation influences the performance of the Head of Government employees at the Karang Binangun Belitang Madang Raya Ogan Komering Ulu Timur Village Office. The aim of this research is to determine the effect of motivation on the performance of Government Section Head employees at the Karang Binangan Belitang Madang Raya Ogan Komering Ulu Timur Village Office and to be useful as reference material for further research regarding employee motivation and performance. The hypothesis proposed is that motivation has a positive effect on the performance of the Head of Government employees at the Karang Binangun Belitang Madang Raya Ogan Komering Ulu Timur Village Office. Data collection and processing using library studies and field studies using observation, questionnaires, interviews and documentation. From the results of the discussion, it was found that the correlation between motivation in efforts to improve the performance of Government Section Head employees at the Karang Binangun Belitang Madang Raya Ogan Komering Ulu Timur Village Office obtained an r figure of 0.68. After consulting with conservative standards, it is between 0.600-0.799 which is considered a strong correlation. So it can be said that there is a strong influence between motivation on the performance of Government Bureau employees at the Karang Binangun Belitang Madang Raya Ogan Komering Ulu Timur Village Office.